Landownership and the gender gap in agriculture: Disappointing insights from Northern Ghana - Yokying, Phanwin; Lambrecht, Isabel B. (International Food Policy Research Institute, 2019)
Land provides the basis for food production and is an indispensable input for economic livelihoods in rural areas. Landownership is strongly associated with social and economic power, not only across communities and households, but also within households. The link between landownership and women’s empowerment has been relatively well documented in general, but not specifically in relation to agriculture. This paper aims to fill this gap by analyzing how ownership of land is associated with agency and achievements in agriculture among female and male farmers in northern Ghana, a region transitioning from customary land tenure without individual ownership rights towards a more individualized and market-based tenure system. We use a recursive bivariate probit model and focus on eight different indicators in four distinct domains: decisions on agricultural cultivation, decisions on farm income, agricultural association membership, and time allocation. Our empirical estimates indicate that landownership is positively correlated with men’s and women’s agency in agriculture, namely in decisions on agricultural cultivation and membership in agricultural association. Yet, we also find that the gender gaps in participation in cultivation decisions, the use of agricultural earnings, and in agricultural workload continue to persist among those who own land. While the results underscore the importance of land as a resource that can enhance women’s agency, they also point out that policies aiming to solely advance land rights may not be sufficient to eradicate or even reduce gender inequality in agriculture.